Dark chocolate: understanding the impact of limonene on the crystallization properties and application of green leaf lipid extract as a flow enhancer - MOHAMAD, NIZAHA JUHAIDA (2017)
Dark chocolate as the main subject matter in this study was investigated for physical changes when formulated with two different lipids based ingredients impacting on the chocolate flow properties. The first ingredient was limonene, known to reduce viscosity when substituting a small fraction of the cocoa butter and to affect cocoa butter crystal morphology, but without knowledge of the impact on bloom formation. The second lipid ingredient was a polar lipid extract from green leaf tissue hypothesised to show functionality as a flow aid, potentially enabling the replacement of currently applied commercial surfactants in chocolate. The driver for this part of the PhD study was to uncover alternatives for the commercial surfactant polyglycerol polyricinoleate (PGPR) which has a negative consumer image. This study was also carried out to devise an opportunity for functionalisation of green tissue waste, although in this first investigation, fresh spinach was used as the raw tissue material. As DGDG was claimed to be the polar lipid compound that caused the low viscosity reduction of dark chocolate by oat lipids, DGDG as well as MGDG are also available abundantly in spinach. The limonene work was using the techniques of whiteness index (WI) to detect bloom, X-ray diffraction (XRD) for crystal identification and differential scanning calorimetry (DSC) for the melting behaviour. Limonene significantly influenced the cocoa butter crystal transformation rate in chocolate which further promoted the development of clearly visible bloom. Nevertheless, limonene may still commercially can be applied in chocolate filling or white chocolate bars where bloom formation is not visible. Polar green leaf tissue lipids were extracted from both spinach leaf and spinach chloroplast due to their difference in composition. Based on compositional analysis of the lipids and their fatty acids by thin layer chromatography (TLC) and gas chromatography (GC), respectively, it was confirmed that leaf contained higher proportion of phospholipids compared to chloroplast, which was highly concentrated with glycolipids. The surface active nature of both lipid extracts was confirmed by interfacial tension measurements at the oil/water interface. Leaf and chloroplast lipid showed a comparable surface activity and demonstrated to be more surface active than lecithin and PGPR. Before applying as flow aid into a complex chocolate formulation, sugar/oil suspensions with added surfactant were rheologically analysed. The performance of the two green tissue extracts was compared to the commercially applied lecithin and PGPR in a concentration range of 0.1 % to 0.7 % based on total suspension containing between 40 and 50 % sugar by weight. Both spinach leaf and chloroplast lipids showed a comparable result in influencing the rheological properties of chocolate model. Therefore, due to the higher lipid recovery from leaf compared to chloroplast as the basic of parent leaf, application in chocolate to verify the results obtained for the model system was executed only for leaf lipid extract. Based on the model suspension results addition at 0.3 and 0.6% on chocolate by weight was considered. Spinach leaf lipid decreased the viscosity of chocolate to value lower than lecithin and PGPR added at the both levels. Yield value measured at 5 s-1 was also reduced; at both levels of addition providing an advantage over lecithin which was shown and is known to increase yield stress at higher level of addition. On the other hand, the yield (5 s-1) lowering capacity was less pronounced than PGPR whereas it was found to be effective based on the model chocolate system. The present results show promise for green leaf tissue lipid to be applied as surfactant in chocolate or fat based food suspension although further research is required to develop the full potential of this natural surfactant system.